Dictyostelium Differentiation-Inducing Factor-1 Binds to Mitochondrial Malate Dehydrogenase and Inhibits Its Activity - Tomoko Matsuda; Fumi Takahashi-Yanaga; Tatsuya Yoshihara; Katsumi Maenaka; Yutaka Watanabe; Yoshikazu Miwa; Sachio Morimoto; Yuzuru Kubohara; Masato Hirata; Toshiyuki Sasaguri (Elsevier, 2010)
We have reported that the differentiation-inducing factors (DIFs) DIF-1 and DIF-3, morphogens secreted from Dictyostelium discoideum, inhibit proliferation of several cancer cells via suppression of the Wnt/ β-catenin signaling pathway. However, the target molecules of DIFs involved in the anti-proliferative effects are still unknown. In the present study, DIF-1-tethered resins were synthesized to explore the target molecules of DIFs, and mitochondrial malate dehydrogenase (mMDH) was identified as one of the target molecules. In the in vitro assay, DIF-1 and other analogs including 2-MIDIF-1, DIF-3, and 6-MIDIF-3 were found to be capable of binding to mMDH but not to cytoplasmic MDH. However, only DIF-1 and 2-MIDIF-1 inhibited the enzymatic activity of mMDH. The effects of DIF analogs on ATP content and cell proliferation were then analyzed using HeLa cells. DIF-1 and 2-MIDIF-1 were found to lower the ATP content and both chemicals inhibited HeLa cell proliferation, suggesting that inhibition of mMDH activity affected cell energy production, probably leading to the inhibition of proliferation. These results suggest that the inhibition of mMDH activity by DIF-1 and 2-MIDIF-1 could be one of the mechanisms to induce anti-proliferative effects, independent of the inhibition of the Wnt/ β-catenin signaling pathway. Keywords:: differentiation-inducing factor, mitochondrial malate dehydrogenase (mMDH), energy production, ATP content, cell proliferation